A novel and effective strategy for producing core-shell LiNiPO4/C cathode material for excellent electrochemical stability using a long-time and low-level microwave approach. (September 2016) - Örnek, Ahmet; Kazancioglu, Mustafa Z.
Abstract: Nanostructured LiNiPO4 /C core-shell composites were synthesized by a newly elaborated long-time and low-level microwave-solvothermal route in the presence of an alginic acid as a carbon precursor. This unusual microwave approach is simple and effective; it clearly improves crystal qualities compared to conventional processes. This study on the influence of the synthesis methodology on electrochemical properties is focused in terms of the cycle stability and rate performance. These are problems for LiNiPO4 cathodes which have not yet been overcome. Thus, an analysis is presented with regard to the ability to create increased energy storage for today's high-powered portable devices. Graphical abstract: